DISSOLUTION ENHANCEMENT OF A POORLY SOLUBLE MODEL DRUGS USING DIFFERENT FORMULATION APPROACHES FOR IMMEDIATE RELEASE SOLID DOSAGE FORM - Srivastava, Vikas; Mishra, Garima (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The purpose of this study was to endeavor Bilayered tablets (SNFML) and to enhance the in vitro release rates. Several techniques were comparing for improving the dissolution of model drugs SNFML (poorly soluble drugs). Particle size reduction was done by jet milling (Micronization of SNML), use of solubility enhancers like Klucel-Lf and sodium lauryl sulphate, reduction of surface energy by co-sifting and SNML with lactose showed the immediate release profile when compared with the unmicronized drug. Micronization of SNML improved its dissolution rate in Discriminative media (8.2percent in 30 min) compared to unmicronized drug (1.3percent in 30 min). SNML drug products commercially available on the global markets dissolved similarly to unmicronized SNML, but significantly slower than the micronized drug. The results recommend that Micronization, use of solubility enhancers and reduction of surface energy by co-sifting are powerful traditions for the preparation of immediate release formulations of SNFML, and could potentially show the way to improvements in the bioavailability of oral SNFML products. Key Words: Poorly water-soluble drugs; Dissolution enhancement; Hydrophilic polymers, Micronization; SNFML